THU0240 Dysregulations in The Sphingolipid Pathway in SLE Patients. (15th July 2016) - Checa, A.; Idborg, H.; Sar, D.G.; Jakobsson, P.-J.; Wheelock, C.E.; Gunnarsson, I.
Abstract : Background: Systemic lupus erythematosus (SLE) is an autoimmune disease with a heterogeneous presentation of symptoms from joints, skin, kidneys, central nervous system, lungs, and the cardiovascular system. There is no cure for SLE and development of novel drugs and biomarkers of effective treatment is needed. Sphingolipids are bioactive signaling molecules involved in the regulation of cell growth, differentiation and apoptosis. Dysregulation of single sphingolipids has been described in several diseases with an inflammatory component and sphingosine-1-phosphate (S1P) agonist (Fingolimod) is investigated as treatment in SLE. Therefore, the sphingolipid pathway has arisen as very important compounds to study in respect to SLE pathogenesis. The compounds of the sphingolipid pathway are highly correlated and simultaneous measure of several sphingolipids in an "omics" like analysis is expected to provide more information than compounds individually determined. Objectives: Our objective is to screen the sphingolipid pathway in patients with SLE compared to healthy controls. In addition we aim to study if the altered sphingolipids will be normalized after treatment. Methods: EDTA-plasma from 107 SLE female patients were screened for 34 different sphingolipids by liquid chromatography tandem mass spectrometry (LC-MS/MS) and compared to matched healthy population-based donors (n=23). In addition, female SLE patients (n=22) were analyzed before and after induction of remission treatment. Results: SLE patients were found to exhibit an altered sphingolipid profile compared to controls. Significantly (p<0.01) increased levels of C16:0- and C24:1-ceramides, C16:0, C18:0 and C24:1-hexosylceramides and decreased levels of S1P were found in SLE patients compared to controls. The observed higher levels of ceramide to S1P ratios in SLE patients may reflect the blockage of the pathway that is controlled by ceramidase and can be inhibited by nitric oxide. These alterations were associated with SLAM and SLEDAI clinical scores and were normalized after induction of remission treatment. Conclusions: This work shows the importance of performing a holistic approach targeting the different molecules of the sphingolipid pathway. Our results show dysregulations in circulating sphingolipids in patients with SLE and normalized after treatment, suggesting that sphingolipids may be useful markers of disease progression and possible drug targets. Disclosure of Interest: None declared